Minimal spanning tree for 100 companies in Bursa Malaysia - Bahaludin, Hafizah; Abdullah, Mimi Hafizah; Mat Salleh, Supian (2014)
This paper investigates the stock market network among the stocks traded in Bursa Malaysia by using minimal spanning tree (MST) techniques. The daily closing prices from 2011 until 2013 of 100 companies based on market capitalization are chosen to construct the network. By constructing the stock market network, the most influential stocks in Malaysian stock market are identified by employing the centrality measurements which are degree, betweenness and closeness. The findings of this study ascertain that from the 100 companies studied, four companies are identified as the most influential in the Malaysian stock market.